3D gel printing of magnetic hydrogel scaffolds assisted by in-situ gelation in a water level-controlled crosslinker bath. Issue 10 (15th May 2023) - Duan, Jing; Lin, Tao; Liu, Hongyuan; Xu, Jing; Shao, Huiping
Abstract: Polyvinylalcohol/chitosan (PVA/CS) is an excellent dual-network hydrogel material, but some significant challenges remain in fabricating composites with specific structures. In this study, 3D gel printing (3DGP) combined with a water-level controlled crosslinker bath was proposed for the rapid in-situ prototyping of PVA/CS/Fe3 O4 magnetic hydrogel scaffolds. Specifically, the PVA/CS/Fe3 O4 hydrogels were extruded into the crosslinker water to achieve rapid in-situ gelation, improving the printability of hydrogel scaffolds. The effect of the PVA/CS ratio on the rheological and mechanical properties of dual-network magnetic hydrogels was evaluated. The printing parameters were systematically optimized to facilitate the coordination between the crosslinking water bath and printer. The different crosslinking water baths were investigated to improve the printability of PVA/CS/Fe3 O4 hydrogels. The results showed that the printability of the sodium hydroxide (NaOH) crosslinker was significantly better than that of sodium tripolyphosphate (TPP). The magnetic hydrogels (PVA: CS= 1: 1) crosslinked by NaOH had better compressive strength, swelling rate, and saturation magnetization of 1.17 MPa, 92.43%, and 22.19 emu/g, respectively. The MC3T3-E1 cell culture results showed that the PVA/CS/Fe3 O4 scaffolds promoted cell adhesion and proliferation, and the scaffolds crosslinked by NaOH had superior cytocompatibility. 3DGP combined with a water-level controlled crosslinker bath offers a promising approach to preparing magnetic hydrogel materials.